2009
DOI: 10.1159/000268128
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flora in Inflammatory Bowel Disease

Abstract: The pathogenesis of inflammatory bowel disease (IBD) involves an interaction between host susceptibility (which is partly genetically determined), mucosal immunity and the intestinal milieu. Micro-organisms have physiological effects on mucosal structure, epithelial turnover, the intestinal immune cells and, thus, on many intestinal functions. Toll-like receptors and nucleotide oligomerisation-binding domain proteins in host cells recognise specific bacterial molecules and modify the immune response. Human stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 88 publications
2
33
1
Order By: Relevance
“…Similar results have been reported in earlier studies [63][64][65]. The Clostridium leptum subgroup was reduced non-significantly in CD patients but increased sharply in UC patients, as observed in earlier studies [65][66][67]. The difference was more pronounced between UC and CD patients.…”
Section: Gut Flora and Inflammatory Bowel Diseasesupporting
confidence: 91%
“…Similar results have been reported in earlier studies [63][64][65]. The Clostridium leptum subgroup was reduced non-significantly in CD patients but increased sharply in UC patients, as observed in earlier studies [65][66][67]. The difference was more pronounced between UC and CD patients.…”
Section: Gut Flora and Inflammatory Bowel Diseasesupporting
confidence: 91%
“…The losses of normal intestinal bacterial taxa, such as Bacteroides, Lactobacillus, Ruminococcus, and Bifidobacterium, observed by us supported earlier observations (3,11,16,27) proving the hypothesis that loss of commensal organisms profoundly modifies gut mucosal homoeostasis through loss of essential micronutrients (short chain fatty acids) and redox potential (2). The Clostridium leptum subgroup was reduced nonsignificantly in CD patients but increased sharply in UC patients (P ϭ 0.0155), as observed earlier (9,18,27). The difference was more pronounced between UC and CD patients (P ϭ 0.0118).…”
supporting
confidence: 59%
“…Using a wide range of different techniques, changes in the population diversity of both the luminal and mucosa-associated microbiota have been demonstrated. Luminal changes were mainly associated with a decrease in the diversity of the Firmicutes, in particular Lactobacilli and Clostridia, and Bacteroidetes (Manichanh et al, 2006;Marteau, 2009;Scanlan et al, 2006;Sokol et al, 2009), while an increase in the Enterobacteriaceae population was reported for CD (Seksik et al, 2003). All reports described a reduced diversity of the mucosa-associated microbial communities in IBD.…”
Section: The Role Of Gut Bacteria In Immune Homeostasismentioning
confidence: 96%